Peran Literasi Digital dalam Menangkal Penyebaran Hoaks di Platform Media Sosial - Karya Mahesa; Faizal Pandapotan Siregar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The rapid development of digital technology has positioned social media as the primary channel for information dissemination. However, this condition has also intensified the spread of hoaxes, which threaten social integration and democratic quality. This study aims to analyze the role of digital literacy in preventing the dissemination of hoaxes on social media platforms. The research employs a qualitative descriptive approach through library research, utilizing secondary data from scientific journals, official reports, and credible media sources. The findings indicate that digital literacy serves as a crucial competency in enhancing individuals’ ability to critically evaluate information, recognize misinformation, and act responsibly in digital communication. Furthermore, low levels of digital literacy contribute significantly to the widespread circulation of hoaxes, driven by algorithmic systems and emotional engagement patterns. Strengthening digital literacy, particularly in cognitive, ethical, and critical dimensions, is proven to improve societal resilience against disinformation. Therefore, integrating digital literacy into formal education, community-based programs, and multi-stakeholder collaboration is essential to effectively combat hoaxes in the digital era.